Is nitrogen accumulation in grain legumes responsive to growth or ontogeny? - Marrou, H.; Ricaurte Oyola, José Jaumer; Ghanem, Michel Edmond; Clavijo Michelangeli, José A.; Ghaouti, L.; Rao, Idupulapati M.; Sinclair, Thomas R. (Wiley, 2018)
Nitrogen (N) accumulation in legumes is one of the main determinants of crop yield. Although N accumulation from symbiotic nitrogen fixation or N absorption from the soil has been widely investigated, there is no clear consensus on timing of the beginning of N accumulation and the termination of N accumulation and the physiological events that may be associated with these two events. The analyses conducted in this study aimed at identifying the determinant of N accumulation in two grain legume species. Nitrogen accumulation dynamics and mass accumulation and development stages were recorded in the field for several genotypes of common bean (Phaseolus vulgaris) and faba bean (Vicia faba) under different growing conditions. This study showed that during the vegetative stages, N accumulation rate was correlated with mass accumulation rate. However, the maximum accumulation of N did not correspond to the time of the maximum mass accumulation. In fact, for both species, N accumulation was found to persist in seed growth. This challenges a common hypothesis that seed growth causes a decrease in N accumulation because of a shift of the photosynthate supply to support the seed growth. Even more surprising was the shift of the active accumulation of N in faba bean to late in the growing season as compared with common bean. N accumulation by faba bean only was initiated at high rates very late in vegetative growth and persisted at high rates well into seed fill.